Validity and Reliability of the Questionnaire of Role Ambiguity in Greek Team Sports - Karamousalidis, Γεώργιος; Laparidis, Κωνσταντίνος; Galazoulas, Χρήστος; Bebetsos, Ευάγγελος (Inquiries in Physical Education and Sport, 2009)
The purpose of this study was to investigate the use of the questionnaire of Role Ambiguity (Role Ambiguity Scale, Beauchamp et al., 2002), in offensive and defensive responsibilities, of Greek Team Sports’ athletes, by checking its structural validity and reliability. The sample consisted of 411 athletes, basketball, volleyball, handball and soccer. Reliability analysis confirmed satisfactory Cronbach’s alpha rates from .76 to .86. At the same time, through confirmatory factor analysis, four factors were found: The Scope of the Responsibilities, Role Behavior, Role Evaluation and Role Consequences both in offending and defending. In conclusion, the results confirmed the reliability and structural validity of the questionnaire regarding its use in Greek Team Sports’ settings.